Bacillus species for controlling root-knot nematodes in development in sugar cane - Ferreira, R. J. [UNESP]; Soares, P. L. M. [UNESP]; Carvalho, R. B. de [UNESP]; Santos, J. M. dos [UNESP]; Batista, E. S. P. [UNESP]; Barbosa, J. C. [UNESP] (Organization Trop Amer Nematologists, 2017)
Root-knot nematodes cause significant loss and may decrease the productive life of sugar cane in a field. The predominate method for the management of root-knot in sugar cane is by nematicides that face increasing restrictions. Biological control has the potential as an alternative control method. Bacillus spp. were evaluated for the control of Meloidogyne incognita and M. javanica in sugar cane seedlings. Seedlings of sugar cane cultivar 'RB 86-7515' were planted individually into 10-L pots containing sterilized coarse sand/soil (2: 1). Applications of B. subtilis (1 x 10(8) U.F.C / mL, 10 L/ha), B. firmus (1 x 10(8) U.F.C / mL, 10 L/ha), B. amyloliquefaciens (1 x 10(8) U.F.C / mL, 10 L/ha), and Carbofuran 350 SC (5 L/ha) were made and the seedlings inoculated with 5,000 eggs and second stage juveniles (J2) of M. incognita or M. javanica. The control consisted of inoculated plants untreated with bacteria or nematicide. At 100 and 150 days after applying the treatments, plant height, plant weight, root weight, numbers of tillers, and quantity of eggs, and J2 of M. incognita and M. javanica in the roots of each plant were evaluated. In the pot assay, all treatments increased the number of tillers, but did not affect the number of nematodes recovered.
Keywords: biological control; Meloidogyne incognita; Meloidogyne javanica; Saccharum sp.